Handbook on family and community engagement - Redding, Sam; Murphy, Marilyn; Sheley, Pamela (Emerald Publishing Limited : Information Age Publishing, Inc., 2011)
Thirty-six of the best thinkers on family and community engagement were assembled to produce this Handbook, and they come to the task with varied backgrounds and lines of endeavor. Each could write volumes on the topics they address in the Handbook, and quite a few have. The authors tell us what they know in plain language, succinctly presented in short chapters with practical suggestions for states, districts, and schools. The vignettes in the Handbook give us vivid pictures of the real life of parents, teachers, and kids. In all, their portrayal is one of optimism and celebration of the goodness that encompasses the diversity of families, schools, and communities across our nation.
Keywords: Education -- Parent participation -- United States.; Home and school -- United States.; Education -- Parent Participation.; Educational administration and organization.; elektronické knihy; electronic books